Poor mental health in severely obese patients is not explained by the presence of comorbidities. Issue 1 (22nd December 2014) - Somerville, R.; McKenzie, K.; Eslami, S.; Breen, C.; O'Shea, D.; Wall, P.
Summary The prevalence of obesity, especially severe obesity where body mass index (BMI) exceeds 40 kg m−2 and where the physical risks are greatest, is increasing. However, little is known about the impact of severe obesity on psychological well‐being and self‐rated health (SRH). We aimed to investigate this relationship in patients attending an Irish weight management clinic. SRH was measured with a single‐item inventory (excellent = 1, poor = 5). Well‐being was measured with the validated World Health Organization‐Five Well‐being Index (WHO‐5), in which scores <13 indicate poor well‐being. Previous studies of the Irish population have reported mean SRH = 2.56 (males) and 2.53 (females) and mean well‐being = 16.96. One hundred eighty‐two (46.8%) completed questionnaires were returned. The sample was representative of the clinic population with a mean age of 47.1, mean baseline BMI of 51.9 kg m−2 and 64.3% females. Mean SRH was 3.73 in males and 3.30 in females; mean well‐being was 10.27 in males and 10.52 in females. In the final multivariable models, number of medications, depression and obstructive sleep apnoea, WHO‐5 and current BMI were significant predictors of SRH, and secondary level education, social support and mindfulness scores were significant predictors of psychological well‐being. Number of medications was not significant. The results suggest that the poor psychological well‐being seen is not explained by the presence of comorbidities and that social support and mindfulness may be important targets for improving psychological well‐being. Improving psychological well‐being in addition to weight loss and effective management of comorbidities may be important for improving SRH.